The Innovation of Consumption Code Innovation Set Off by The Sharing Economy：Xianyu Platform as An Example: 共享经济掀起的消费符码革新——以闲鱼为例 - FENG , Lang (Mandarinable: Journal of Chinese Studies, 2022)
As a new economic phenomenon that has been hotly discussed in recent years, the sharing economy has shown the characteristics of being in line with the “The Fourth Consumption Era", including the idle economy that also become a concern. By combining the experience of individual consumption, platform, industry competition, and the macro environment with Baudrillard's theory of consumer society, this article analyzes the generation and operation logic of the functional groups and promotes an innovative approach to consumption code. From the perspective of the customer society, the current situation of sharing economy is still promoting increasing the consumption culture and deepening the awareness of consumption.